Chiasmal apoplexy: haemorrhage from a cavernous malformation in the optic chiasm. Issue 9 (September 1989) - Regli, L; de Tribolet, N; Regli, F; Bogousslavsky, J
Abstract : We present a patient who experienced sudden onset of orbital headache, visual loss and bitemporal visual field defect. MRI of the optic chiasm suggested a diagnosis of haemorrhage and hence a vascular malformation. Pterional craniotomy revealed an intrachiasmatic haematoma with a cavernous angioma. The malformation was totally excised and vision improved after surgery. The syndrome of chiasmal apoplexy is discussed.